"Let's kill him": self-reference pronouns and speaking roles in capital trials. Issue 4 (8th August 2021) - Chaemsaithong, Krisda; Kim, Yoonjeong
ABSTRACT: Viewing pronouns as a semiotic resource that is central to self/other positioning, this study explores constitutive and performative functions of self-reference pronouns in the institutional context of the penalty phase of capital trials. Based on a corpus of 12 closing arguments, the findings indicate that self-reference pronouns are not simply indexical tools of reference in this monologic discursive event but also serve to activate and foreground certain identities while backgrounding others. In effect, lawyers can orchestrate a multiplicity of selves, ground their participation as members of different socio-cultural communities other than that defined by the current setting, and shift their speaking roles and perspectives in relation to the audience and the issue being discussed on a moment-by-moment basis. Such manipulation of group membership constitutes power struggles between opposing lawyers in the efforts to display (dis)alignment with aggravating and mitigating factors, alienate or create empathy for the person on trial, and manage self-impression and relationship with the jury, thereby potentially mediating capital jurors' perceptions of state killing.